Role of Hand and Foot Print Dimensions in Stature Identification among Indian Population (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: The four essential factors in Forensic Anthropology, representing in determining personal identificationare age, sex, stature and ethnicity. Among this ‘big fours’ of the biological profile, determination of stature isconsidered as one of the main parameter of personal identification in forensic examinations. Thus, this study will aimto correlate relation between hand and foot measurements with stature of individual.Aim of the study: The study aimed to estimate the relationship between statures of an individual on the basis of handand foot prints, in Indian populations.Materials and Method: The study group comprised of 100 subjects (age group above 18 years) with normal growthand development.Measurement of height: The measurements of height was made using standard anthropometer by making the subjectstand erect on the horizontal plane. The distance of the subject from the ground to the highest point of the vertex inthe median sagittal plane was recorded.a) Hand length and Hand breadth: Hand length (HL) was measured from mid-point below radial and ulnartuberosity to tip of middle finger. Hand breadth (HB) was measured from base of 5th to 2nd metacarpus by drawingthe outline of hand on paper.b) Foot length and breadth: The foot length was measured as a direct distance from the most posterior pointof back to tip of the Hallux or to tip of the second toe .The foot breadth was measured as the direct distance betweenthe most prominent point on medial side and the most prominent on lateral side.d) Heel Ball Index Measurement The breadth of the foot at ball and at heel (BBAL, BHEL) were measured. The HB Index of the foot was calculatedas (BHEL+ BBAL) x 100.Results: Correlation of the various hand and foot parameters showed a regression coefficient range of 0.331-0.377.Among all variables measured, hand length exhibited the highest correlation with stature (r value of 0.377 p-value <0.003). Further forward stepwise linear regression analysis [Height = 115.426+2.615* Hand length (Left)] establishedhand length to be the single best predictor of height (r value of 0.377 and standard error of 7.35cms).Conclusion: Thus, the foot length provides highest reliability and accuracy in estimating stature of unknown malesand females. Also this study will help to generate population-specific equations using a simple linear regressionstatistical method.